Isolated alimentary tract duplication presenting as a prenatal abdominal cyst - Shota Ebinuma; Go Ohba; Masato Nakayama; Hiroshi Yamamoto (Elsevier, 2018)
Background: Alimentary tract duplication is a congenital malformation that can occur along the normal alimentary tract. We experienced a rare case of alimentary tract duplication that didn't share the muscle layer with the normal alimentary tract. Case presentation: A female infant was delivered by caesarean section at 35 weeks 6 day because of growing neonatal abdominal cyst. Emergency operation was performed on the birth day to improve abdominal bloating and breathing problem. At surgery, there was a cyst with feeding vessel coming from mesentery of the ascending colon and cystectomy was performed. The cystic wall had a well-developed smooth muscle layer with a gastric mucosal lining, and we diagnosed the completely isolated alimentary tract duplication. Conclusion: We experienced a very rare case of completely alimentary tract duplication. This anomaly is reported 20 cases in the world to the best of our knowledge. The prognosis of this is good, but resection is recommended because of malignancy. Keywords: Alimentary tract duplication, Prenatal diagnosis, Abdominal cyst, Neonatal surgery